Assessing the Planning and Design of Sulaimani City Entrances An Evaluative Approach - Hisham Taher Al Jarah, Sivan; Jalil Abdulla, Rebaz (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The entrances to the city play a crucial role in captivating visitors as they arrive in each urban area. These entry points are anticipated to symbolize the city’s physical, cultural, social, and historical traits, serving as sources of inspiration for those who enter. They serve as the initial point of contact, setting the tone for the urban experience that follows. A well-designed city entrance should not only be aesthetically pleasing but also functional, safe, and reflective of the city’s unique identity. The entrance serves as a window to the perception of the city’s landscape and is an element that requires semantic consideration in terms of perception. The purpose of this study is to grab the attention and examine the importance of city entrances that have been neglected. While the first image of the city taking by the residents and visitors is through the city entrance. Therefore; paying attention and redevelop entrances of the cities reflect a right and a pleasant image about the cities. In addition; enhancing various historical, natural, environmental, cultural and economic prices of the city. This study conducting Sulaymani city in Iraq as a case study employed a mix-method in analyzing present and future scenario of city entrances in term of several variation (entrance as a symbol of a city, entrance as a mental boundary of a city and entrance as a window to look at a city). The finding of the study shows that the city of Sulaimani main entrances fail to showcase the city’s unique identity and cultural heritage. This deficiency holds considerable implications for both inhabitants and those who visit the city. Furthermore, the study revealed significant deficiencies across various domains, encompassing planning and design strategies, infrastructure and transportation facilities, land use and zoning patterns, as well as cultural and social considerations. Finally, a notable issue lies in the absence of clearly defined entrances and their actual responsibility in establishing a distinct boundary between the exterior and interior of the city.